2018
DOI: 10.1021/jacs.8b02016
|View full text |Cite
|
Sign up to set email alerts
|

TiC3 Monolayer with High Specific Capacity for Sodium-Ion Batteries

Abstract: Sodium-ion batteries (SIBs) have attracted considerable attention due to the intrinsic safety and high abundance of sodium. However, the lack of high-performance anode materials becomes a main obstacle for the development of SIBs. Here, we identify an ideal anode material, a metallic TiC monolayer with not only remarkably high storage capacity of 1278 mA h g but also low barrier energy and open-circuit voltage, through first-principles swarm-intelligence structure calculations. TiC still keeps metallic after a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
223
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 277 publications
(228 citation statements)
references
References 80 publications
(134 reference statements)
3
223
0
2
Order By: Relevance
“…Moreover, improving the carbon chemical compositions in Mo 2 C is anticipated to raise total Li storage capacity yet preserving the unique attributes of molybdenum carbide materials, since some recent pioneering work revealed that interactions between carbon and lithium contribute significantly to Li + accommodations of TMCs . Whereas, due to limited synthesis method to prepare carbon‐rich TMCs, understanding the interfacial interaction effect on the high‐rate performance of TMCs is often neglected in previous research.…”
supporting
confidence: 89%
“…Moreover, improving the carbon chemical compositions in Mo 2 C is anticipated to raise total Li storage capacity yet preserving the unique attributes of molybdenum carbide materials, since some recent pioneering work revealed that interactions between carbon and lithium contribute significantly to Li + accommodations of TMCs . Whereas, due to limited synthesis method to prepare carbon‐rich TMCs, understanding the interfacial interaction effect on the high‐rate performance of TMCs is often neglected in previous research.…”
supporting
confidence: 89%
“…The adsorption of Na atoms with high concentration on one side of the above MXenes was used to explore the high storage capacity for Na atoms. The DFT calculation information is provided in the Supporting Information . The initial structures of bare, O‐, F‐, S‐functionalized Ti 3 C 2 (the same symmetry group P ‐3 M 1) were fully relaxed, and the optimized structure data were listed in Table S2 in the Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…[52] Recently,m uch effort has been devoted to improving Na + ion storage of MXenes by controlling nanosheet thickness and the rational design of hierarchical porouss tructures. DFT calculationsi dentified that the dynamic and thermals table TiC 3 monolayer with metallic behavior has av ery high theoretical specific capacity with av alue up to 1278 mAh g À1 for aS IB anode, [53] which is three times highert han that for Ti 2 C (359 mAh g À1 ) [50b] or Ti 3 C 2 (370 mAh g À1 ). [54] The metallicn ature of TiC 3 was retained even after adsorbing two layers of Na atoms, indicating good electrical conductivity and ultralong cycle life.…”
Section: Mxenes-based Materials For Sibsmentioning
confidence: 99%